Myanmar Country Environmental Analysis : Forest Resources Sector Report - World Bank (World Bank, Washington, DC, 2019)
Myanmar's forest and timber sector has been central to the country's economy and society, particularly over the last century. Myanmar's forests contain some of the most valued species in the world—particularly rosewood, ironwood, and teak. Myanmar also has one of the most longstanding forest management systems in the tropics. Today, despite reduced timber extraction revenues, wood industry still generates over 8 percent of formal government revenues. Beyond timber, rural society largely depends on non-timber forest products (NTFPs) and agroforestry for food, medicine, and wood fuel, which is by far the most important energy source in rural Myanmar, with between 60 percent and 80 percent of communities relying on this source. Some of Myanmar's forests also form some of the world's most critically important biodiversity 'hotspots'. Despite all of the progress made, there is still a lot of room for improvement and for higher ambition. The report analyzes the underlying challenges, builds on international best practice, and makes recommendations. Some of the recommendations include : create delivery mechanisms to scale up CF within the PFE, despite high degradation of production forests, sustainable forest management is still viable in some areas but needs a critical stock-taking effort, promote enabling environment for private plantations, increase protected forests area to 10 percent of total land area, and to implement the challenging reform process, the FD will need additional skills, budget, technology support, and civil society support.